Perbedaan Kadar Asam Urat Sebelum dan Setelah Pemberian Jeroan pada Tikus Putih - Desto Arisandi; Syeun Nurochman; Subrata Tri Widada (LPPM STIKES Guna Bangsa, 2015)
Background: The era of globalization has brought many changes to lifestyle and eating habits are not healthy in the community. High protein foods that contain lots of purines can cause hyperuricemia. The aim of this study was to determine differences in the uric acid levels of before and after given of offal in the mice. Method: A true experimental study with pretest-posttest control group design used 14 mice. Data collection from measurements in the uric acid levels in the blood of mice examined before and after given of offal chicken liver juice. Analysis of research data was used dependent of paired t-test with confidence level of 95% using SPSS. Result: An average uric acid level before gift of the offal is 3.41 mg/dL, and after to gift of the offal is 7.93 mg/dL. Uric acid levels after to given of offal increased by 4.52 mg/dL (56.99%). In analysis univariate showed differences between uric acid levels before and after to gift of offal chicken liver juice in the mice (p-value = 0.000). Conclusion: There are differences in uric acid levels before and after given of offal in the mice.